Análises genéticas em progênies de Pinus caribaea Morelet var. caribaea por caracteres quantitativos e marcadores moleculares - Silva, Janete Motta da [UNESP] (2005)
This work aimed: to estimate the genetic variability to growth characters and the wood density; to estimate the genetic value of superior trees; to characterize by molecular markers (RAPD e SSR), three groups of individuals - superiors, intermediates and inferiors, selected with multi-effects index; to verify the effect of thinning on progeny trial relating it to parameters genetics; to estimate the gain expected through the use of IME, aiming to turn the progeny trial in a seedling seed orchard and/or to supply material to establish a clonal seed orchard; to give subsidies to genetic breeding program of this species. The results were: a) a genetic variation verified on the traits was few expressive; b) the thinning showed perspectives to these progenies trial to be explored as a seed orchard by seedling and/or clonal; c) the heritability estimates had presented low magnitude and little variation through time; d) the correlations between characters dbh, height and volume was high, and low for wood density and form. The path analysis coefficient was useful to know to correlation among the studied trait, with volume being largely determined by height and little influence by dbh; e) the Mahalanobis generalized distance and the assemble of progenies by Tocher's method gave important information to future breeding programs about hybridization or backcross; f) the multi-effect index applied to dbh, on D situation, showed higher gains than the selection within and among progenies, and the best option the selection up to five plants per progenies because to permit higher gains and keep genetic diversity close to a selection within and among progenies; g) the characterization using molecular markers evidenced homogeneity between the groups of superiors, intermediates and inferiors individuals.